Konsentrasi Logam Berat Cd, Hg, Pb pada Produk Pangan Olahan Berbahan Dasar Pterygoplichthys pardalis (Castelnau, 1855) asal Sungai Ciliwung Wilayah Jakarta - Dewi Elfidasari; Haninah Haninah; Handhini Dwi Putri; Irawan Sugoro (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Backgrounds: Heavy metal that pollutes the river area affects living organisms which reside in it. Contamination of heavy metal in Ciliwung River leads to the presence of heavy metal elements (Cd, Hg, and Pb) inside the body of the plecos (Pterygoplichtys Pardalis) which inhabits that area. Hence, the utilization of plecos flesh and bones as a raw material in processed food products (e.g. shredded fish, shumai, and fish flour) might be harmful for human. Accumulated load of heavy metal in human's body would likely trigger health problems. Insufficient data on heavy metal concentration in Ciliwung River plecos-based food products underlies this research, with the aim to calculate the concentration of heavy metal Cd, Hg, and Pb on the previously mentioned plecos-based shredded fish, shumai, and flour. Methods: Heavy metal Cd, Hg, and Pb concentration analysis using X-Ray Fluoresence (XRF) methods conducted on PAIR Batan. Results: Value of Cd on shredded fish <0.5 mg/kg, shumai 0,7 mg/kg, head+tailbone and body skeleton flour <0.3 mg/kg. Value of Hg on shredded fish and shumai <0.7 mg/kg, head+tailbone flour 0.3 mg/kg, body skeleton flour 0.4 mg/kg. Value of Pb on shredded fish 1.3 mg/kg, shumai 0.8 mg/kg, head+tailbone flour 2.3 mg/kg, body skeleton flour 1.6 mg/kg. Conclusions: Heavy metal concentration on Ciliwung River plecos-based processed food products (shredded fish, shumai, and flour) has exceed maximum limit of Cd, Hg, and Pb determined by SNI, BPOM, and FAO.